Efficient Adsorption of Tetracycline from Aqueous Solution onto Zinc Oxide Nanoparticles: Isotherm, Kinetic, Regeneration and Thermodynamic Studies - Zahraa A. Abd Almajeed; Ahmed A. Mohammed (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
The extracts of the bio-wastes produce from agricultural wastes and plants have been used for the sustainability, eco-friendly and economic synthesis of different metallic nanoparticles. The present study has proposed synthesizing zinc oxide particles (ZnO) by a green chemistry route using waste tea leaves extract to sequestrate tetracycline antibiotic (TEC) from wastewater. The prepared ZnO NPs were characterized using Scanning Electron Microscope (SEM), X-ray Diffraction (XRD), Fourier Transfrom InfraRed (FTIR), Brunauer–Emmett–Teller (BET) surface area, and through the determination of pHpzc. The surface of the ZnO exhibits a highly heterogeneous texture with irregular, aggregated particles and rough surfaces with a BET surface area of 41.7 m²/g. Batch adsorption experiments were conducted, and the results showed that the prepared ZnO NPs could effectively adsorb > 95% of TEC from wastewater at the optimal conditions (pH of 5.5, shaking speed 200 rpm, adsorbent dosage 400 mg/100 ml, temperature 298 K, and 100 ppm initial TEC concentration at 120 min contact time). The kinetics of the adsorption describes well by Pseudo-second order model with a K2 value of 0.004 g/mg-min for a TEC concentration of 100 mg/L, while the mechanism was controlled by external mass transfer and intra-particle diffusion. Langmuir model fitted well the equilibrium adsorption data with a maximum adsorption capacity of 110.56 mg/g, and this provides evidence of a monolayer adsorption phenomenon. Negative ∆H° and ∆G° were indicative of an exothermic and spontaneous nature. Finally, the synthesized ZnO NPs also exhibited good regeneration potential, with only a 31% reduction in efficiency was noticed after five regeneration-adsorption cycles. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).